Research on market consumption prediction based on machine learning - Zhao Xu (E3S Web of Conferences, 2020)
With the rapid development of artificial intelligence industry and big data technology in recent years, the traditional financial industry has gradually transformed into fintech. China Merchants Bank Credit Card Center proposes to rely on data to predict whether users will buy the Pocket Life APP coupons as a practical business scenario. Based on this practical problem, a variety of machine learning methods are used, including logistic regression, random forest. Xgboost, LightGBM, to explore this problem. Finally, an integrated learning method is used to fuse the final result. This paper uses the above several algorithm models for prediction. The model principle is analyzed, and the performance of each model is measured on multiple evaluation indicators. The advantages and disadvantages of different models are compared horizontally, and the reasons for the difference in results are summarized.